REHABILITASI PEMULIHAN NAMA BAIK DEBITOR PAILIT DI INDONESIA - Aliya Sandra Dewi (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2023)
This research aims to find out the debtor can restore his good name in order to restore his good name so that the debtor can still apply for credit again and the process that can be done to restore the good name of a debtor declared Bankrupt by the Court will lose reputation in the eyes of the public. The research method used is normative juridical, with a statutory approach (statue approach), historical approach (historical approach), and case approach (case approach).Based on the analysis and research results that first, the existing bankruptcy regulations are considered unreliable, namely the Civil Code, and Law No.37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations. Because bankruptcy can end with a peace. This peace is carried out by means of an agreement between the bankrupt debtor and the creditors to pay some of their debts first. However, in reality, not all settlements are acceptable. When reconciliation is not acceptable, insolvency becomes the way to end the bankruptcy. The second way to end a bankruptcy is through rehabilitation. Rehabilitation can be accepted if the creditor has received full payment of the debt. Then bankruptcy can be ended by a judge's decision in a higher court level. The judge's decision at a higher court level can revoke the bankruptcy declaration. In addition to these things, there are also things that can make bankruptcy end, namely the revocation of bankruptcy at the suggestion of the supervisory judge. The supervisory judge can give a recommendation to revoke the bankruptcy declaration decision because he knows the financial condition or assets of the bankrupt debtor.